Predictive value of the serum albumin change rate for therapeutic response to targeted therapy in patients with AIDS-related non-Hodgkin lymphoma - Xingzhen, Cheng; Jing, Yang; Tingyu, Chen; Yong, Zhao; Guo, Wei (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to evaluate the predictive value of the serum albumin change rate (Alb Change Rate) for treatment efficacy in patients with AIDS-related non-Hodgkin lymphoma (AR-NHL) undergoing targeted therapy (e.g., rituximab), and to explore the clinical implications of serum albumin (Alb) dynamics during treatment.MethodsThis retrospective study included 95 patients diagnosed with AR-NHL between June 2017 and June 2024. The primary endpoint was the therapeutic response after completion of four cycles of treatment regimens containing targeted agents. Patients were categorized into two groups based on treatment response: effective and ineffective. The objective was to investigate the association between the Alb Change Rate and treatment efficacy in AR-NHL patients. Logistic regression analysis was performed to assess the association between the Alb Change Rate and treatment efficacy. Multivariate analysis was used to adjust for potential confounding variables.ResultsAmong 95 patients with AR-NHL (mean age: 48.99 ± 12.70 years; 78.95% male). The diffuse large B-cell lymphoma (DLBCL) was the predominant subtype (85.26%). According to Ann Arbor-Cotswolds staging, 75.79% were stage III–IV. After four cycles of targeted therapy, 64 patients (67.37%) responded effectively, while 31 (32.63%) were classified as ineffective, including five deaths. The median Alb Change Rate was 3.09% (−34.71 to 78.55%), with corresponding the Hb-Shift and the CD4+Tcell-Shift medians of −5.00 g/L and 10.00 cells/μL, respectively. Common adverse events included gastrointestinal symptoms (92.63%), peripheral neuropathy (92.63%), alopecia (90.53%), pain (43.16%), and bone marrow suppression (32.63%). Univariate analysis showed that Alb Change Rate was significantly associated with treatment response (OR = 116.01; 95% CI: 5.92–2274.51; p < 0.01). Patients with Alb Change Rate ≥ 0 had improved outcomes (OR = 4.31; 95% CI: 1.73–10.70; p < 0.01). This association remained significant after multivariate adjustment (OR = 9.18; 95% CI: 2.73–30.86; p < 0.01).ConclusionThe Alb Change Rate is a useful predictor of treatment response in AR-NHL patients receiving targeted therapy. Alb Change Rate ≥ 0 was significantly associated with better outcomes. These results highlight the value of dynamic Alb monitoring and nutritional support during treatment. Further prospective studies are needed to confirm these findings.